2018
DOI: 10.1016/j.immuni.2018.07.013
|View full text |Cite|
|
Sign up to set email alerts
|

The Kinase IKKβ Regulates a STING- and NF-κB-Dependent Antiviral Response Pathway in Drosophila

Abstract: Antiviral immunity in Drosophila involves RNA interference and poorly characterized inducible responses. Here, we showed that two components of the IMD pathway, the kinase dIKKβ and the transcription factor Relish, were required to control infection by two picorna-like viruses. We identified a set of genes induced by viral infection and regulated by dIKKβ and Relish, which included an ortholog of STING. We showed that dSTING participated in the control of infection by picorna-like viruses, acting upstream of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
155
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(165 citation statements)
references
References 59 publications
9
155
1
Order By: Relevance
“…Furthermore, the induction of AGO2 by CDNs suggest a crosstalk between the two pathways where activation of dSTING potentiates the siRNA response. Intriguingly, our previous results pointed to a specific contribution of the dSTING-IKKβ-Relish pathway in resistance to DCV and CrPV, although a significant but smaller effect was visible also for VSV 5 . This apparent discrepancy could be explained by differences between viruses in the induction of the pathway based on their tissue tropisms, the type of virus-associated molecular pattern produced or the existence of escape strategies, all of which may be bypassed by systemic injection of 2’3’-cGAMP.…”
Section: Discussionmentioning
confidence: 45%
See 3 more Smart Citations
“…Furthermore, the induction of AGO2 by CDNs suggest a crosstalk between the two pathways where activation of dSTING potentiates the siRNA response. Intriguingly, our previous results pointed to a specific contribution of the dSTING-IKKβ-Relish pathway in resistance to DCV and CrPV, although a significant but smaller effect was visible also for VSV 5 . This apparent discrepancy could be explained by differences between viruses in the induction of the pathway based on their tissue tropisms, the type of virus-associated molecular pattern produced or the existence of escape strategies, all of which may be bypassed by systemic injection of 2’3’-cGAMP.…”
Section: Discussionmentioning
confidence: 45%
“…Interestingly, one of the three canonical components of the siRNA pathway, AGO2 , was rapidly induced by 2’3’-cGAMP, together with pst and ref(2)P , which encode restriction factors against picorna-like viruses 22, 23 and rhabdoviruses 24 , respectively. Late induced genes were mainly unknown but included the JAK-STAT regulated gene vir-1 and the antiviral gene Nazo (Fig.2a’’) 5, 25 . Gene ontology analysis revealed that the early and sustained upregulated genes were significantly enriched for a single functional category, namely immunity (Fig.2b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Functional poxin enzymes are also found in the genomes of insect viruses in the family Baculoviridae, and moths and butterflies, which serve as hosts to these viruses [33 ]. The emerging role for cGAS-STING signaling in insects is likely to enable discovery of additional insect pathogen inhibitors of pathway activation [40][41][42]. In mammals, no cytosolic enzymes have been discovered which degrade 2 0 3 0 -cGAMP, but instead the extracellular enzyme ectonucleotide pyrophosphatase/phosphodiesterase family member 1 (ENPP1) has been shown to be the major source of 2 0 3 0 -cGAMPdegrading activity in mammalian tissue and plasma [43].…”
Section: Pathogens Target Cgas To Evade Cytosolic Dna Sensingmentioning
confidence: 99%